Introduksi Teknologi Mesin Penggiling Singkong sebagai Upaya Meningkatkan Kualitas Produk UKM â€œGethuk Bu Sriâ€ Karanganyar Jawa Tengah - Harisudin, Mohd.; Riptanti, Erlyna Wida; Khomah, Isti; Qonita, Rr. Aulia (Jurnal Pengabdian UNDIKMA, 2023)
This community service aims to introduce cassava grinding machine technology to improve the product quality of "Gethuk Bu Sri" Karanganyar, Central Java. The implementation method of this community service is participatory mentoring. The instrument for evaluating this activity is a comparative before-after evaluation and analyzed descriptively. The results of this service show that the grinding machine introduced has a positive impact on business sustainability. Problems in the quality of Gethuk that are not homogeneous can be solved by using this grinding machine. Partner SMEs can use this machine well because they are more experienced and skilled. This positive impact is seen in the quality of Gethuk produced, which is better because it is softer and smoother. The grinding process time is faster, so it is more efficient. The production capacity of Gethuk is more significant because it is more efficient in terms of time and labour.